2017
DOI: 10.1080/21663831.2017.1408713
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermal expansion in the deep super-cooled liquid region of a ZrCuAlAg bulk metallic glass

Abstract: Bulk metallic glasses (BMGs), like other glasses, soften in the super-cooled liquid region (SCLR). Here in this work, surprisingly, a large expansion is reported occurring in the deep SCLR of a Zr 47 Cu 37 Al 8 Ag 8 BMG. Nano-crystals (NCs) are found precipitated during the anomalous expansion of Zr 47 Cu 37 Al 8 Ag 8 , but also in the SCLR of Zr 43 Cu 41 Al 8 Ag 8 that exhibits a conventional softening. It is found that there is a steep composition and density change at the NCs/amorphous matrix transition reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Isothermal annealing of the as-cast sample at 740 K for 5,10,17,18,20,22, and 23 min and successive isochronal DSC scans were conducted to evaluate the thermal properties/structural differences between the heat-treated sample under ambient pressure and the high-pressure heat-treated samples by comparing the crystallization temperature (T x ) and crystallization enthalpy (ΔH cry ). The microstructures of the samples that were isothermally heat-treated at 740 K for 17, 20 and 23 min were examined using TEM.…”
Section: Static Annealing Of the As-cast Sample At Ambient Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Isothermal annealing of the as-cast sample at 740 K for 5,10,17,18,20,22, and 23 min and successive isochronal DSC scans were conducted to evaluate the thermal properties/structural differences between the heat-treated sample under ambient pressure and the high-pressure heat-treated samples by comparing the crystallization temperature (T x ) and crystallization enthalpy (ΔH cry ). The microstructures of the samples that were isothermally heat-treated at 740 K for 17, 20 and 23 min were examined using TEM.…”
Section: Static Annealing Of the As-cast Sample At Ambient Pressurementioning
confidence: 99%
“…Therefore, the total density of the high-pressure heat-treated sample should be higher than that of the partially crystallized sample. Although a few studies have been reported 21,22 , it has been infrequently observed that a fully amorphous sample is denser than the already crystallized sample. The electrical resistivity measurement of the partially crystallized sample was also conducted, as shown in Fig.…”
Section: Creation Of a New Type Of Hidden Anomalous Metallic Glassmentioning
confidence: 99%